Endangered Literacies? Affordances of Paper-Based Literacy in Medical Practice and Its Persistence in the Transition to Digital Technology. (October 2017) - Sterponi, Laura; Zucchermaglio, Cristina; Alby, Francesca; Fatigante, Marilena
Under the rapid advances of digital technology, traditional paper-based forms of reading and writing are steadily giving way to digital-based literacies, in theory as well as in application. Drawing on a study of literacy in a medical workplace context, this article examines critically the shift toward computer-mediated textual practices. While a considerable body of research has investigated benefits and issues associated with digital literacy tools in medicine, we consider the affordances of paper-based practices. Our analysis of verbal interaction and textual artifacts drawn from a qualitative study of oncology visits indicates that the uses of pen and paper are advantageous for both doctor and patient. Specifically, they allow doctors to process and package information in ways that are favorable to their personal modus operandi, and they enable patients to participate in the medical visit and take an active role in managing their medical treatment. Understanding the affordances of paper-based literacy provides insights for refining digital tools as well as for motivating the design of possible hybrid forms and digital-analog intersections that can best support medical practices.